2022
DOI: 10.1039/d1ta09151d
|View full text |Cite
|
Sign up to set email alerts
|

Visible and infrared solar radiation upconversion for water splitting via a surface plasmon-passivated strategy

Abstract: The current photocatalytic technology for water splitting usually localized in specific short-wavelength photons. Herein, we used surface plasmon resonance (SPR) of noble metal to respond to a broad solar spectrum,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Therefore, the chemical structure evolution of C 7 H 8 by one‐step multiple proton coupled electron transfer is thermodynamically more favorable if kinetics permits, thus avoiding the generation of high‐energy free radicals. [ 35 ] This electron tunneling reaction was in accordance with the metal catalysis characteristics, [ 46 ] and Ag‐QDs were considered as the active center of photooxidation.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, the chemical structure evolution of C 7 H 8 by one‐step multiple proton coupled electron transfer is thermodynamically more favorable if kinetics permits, thus avoiding the generation of high‐energy free radicals. [ 35 ] This electron tunneling reaction was in accordance with the metal catalysis characteristics, [ 46 ] and Ag‐QDs were considered as the active center of photooxidation.…”
Section: Resultsmentioning
confidence: 98%
“…[33] Linic et al revealed the underlying mechanistic details of direct plasmon-driven charge transfer through time-dependent in situ surface-enhanced Raman scattering measurements. [34] Direct electron transfer does not suffer from energy dissipation problems (such as electron-electron and electron-phonon scattering), and it is actually a process of electron tunneling with an extremely high electron-hole separation efficiency (excited electrons do not have enough momentum to reverse transfer), [35] exhibiting promising industrial application prospects. However, due to the complexity of plasmonic chemistry, its photocatalytic industrialization still requires many advances in scientific fundamental and practical catalyst research.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13,32 ] Collectively, the modified state of π * electrons could be likely attributed to the non‐covalent dipole–dipole interaction between dipoles of the PDA and dipoles of the oxidized carbon defects. [ 26a,33 ] Consequently, the modified local electronic configuration of carbon defective sites would likely to influence the adsorption/desorption strength of oxygen and ORR intermediates, thereby changing the selectivity of ORR on the CB‐PDA‐A. [ 27,34 ]…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al Reproduced with permission. [80] Copyright 2022, The Royal Society of Chemistry. [34] Copyright 2018, Wiley-VCH.…”
Section: Improving Charge Separationmentioning
confidence: 99%
“…The maximum wavelength of light absorption of g-C 3 N 4 . Reproduced with permission [80]. Copyright 2022, The Royal Society of Chemistry.…”
mentioning
confidence: 99%